Quality of life in breast cancer sufferers. Issue 7 (8th August 2016) - Shouman, Ahmed Essmat; Abou El Ezz, Nahla Fawzy; Gado, Nivine; Ibrahim Goda, Amal Mahmoud
Abstract : Purpose: Measure health related quality of life among patients with early stage cancer breast under curative treatment at department of oncology and nuclear medicine at Ain Shams University Hospitals. Identify factors affecting quality of life (QOL) among these patients. Design/methodology/approach: A cross-sectional study measured QOL among early stage female breast cancer patients and determined the main factors affecting their QOL. Three interviewer administered questionnaires were used. Findings: The physical domain mostly affected in breast cancer patients and the functional domain least. Socio-demographic factors that significantly affected breast cancer patients QOL scores were patient age, education, having children and family income. Specific patient characteristics include caregiver presence - a factor that affected different QOL scores. Age at diagnosis, affection in the side of the predominant hand, postoperative chemotherapy and difficulty in obtaining the medication were the disease related factors that affected QOL scores. Originality/value: The final model predicting QOL for early stage female breast cancer patients included age, education and difficulty in obtaining the medication as determinants for total QOL score. Carer presence was the specific patient characteristic that affected different QOL scores.